PENGARUH KONSERVATISME TERHADAP EFISIENSI INVESTASI DAN AGENCY COST SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR (SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022) - Syahlina Natalia; Chairul Suhendra; Yusmaniarti Yusmaniarti (Universitas Muhammadiyah Bengkulu, 2024)
The purpose of this research is to determine how the influence of conservatism, investment efficiency, and agency cost as moderating variabel in manufacturing companies the date used in this study is secondary data sourced from the annual reports of manufacturing companies listed on the indonesia stock exchange (IDX) the sample size was collected using purposive sampling technique a total of 6 companies the research utilized the SPSS 23 program for windows version 11. The findings indicate that conservatism has a positive impact on investment efficiency, and agency cost do not moderate this positive influence on investment efficiency. Keywords: Conservatism, Investment Efficiency, Agency Cost